Analisis Praktik Utang Piutang Emas Diganti Dengan Uang Tunai Di Desa Larangan Sorjan Kecamatan Klampis Kabupaten Bangkalan - irdlon sahil; R. Rois Albarista; mukarromah mukarromah (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
Debt and receivables of gold replaced with cash is a loan agreement, where the recipient of the loan borrows gold from the lender and the payment benchmark is cash. The purpose of this study was to determine the practice system of gold debt and receivables being replaced with cash and the Islamic economics view of gold being replaced with money. This research design is a qualitative research. The research subjects are the majority of people who are tied to the gold debt case. Methods of collecting data with interviews, observation and documentation, data analysis with qualitative descriptive. Based on the research, it can be stated that in practice gold debt in the Village of Larangan Sorjan, Kec. Klampis Kab. Bangkalan in payment using cash and without being limited to maturity by muqridh, while if viewed from Islamic economic law, it has fulfilled the pillars of debt and receivables and the terms of debt and receivables and in Islam this practice is allowed with predetermined conditions.